Multiband fractal planar inverted F antenna (F-PIFA) for mobile phone application - Saidatul Norlyana, Azemi; Azremi, Abdullah Al Hadi; R. Badlishah, Ahmad, Prof. Madya Dr.; Soh, Ping Jack; Fareq, Malek, Dr. (EMW Publishing, 2010)
Link to publisher's homepage at http://ceta.mit.edu/pierb/index.php